Body Esteem in a Western Australian Cleft Lip and/or Palate Cohort Across 3 Age Groups. (April 2018) - Nicholls, Wendy; Harper, Craig; Selvey, Linda A.; Robinson, Suzanne; Hartig, Gerald; Persson, Martin
Objectives: To determine if patients with cleft lip and/or palate (CL/P) from a Western Australian (WA) cohort were more dissatisfied with their body esteem than a normative non-cleft cohort, and identify demographic variables that may have significant associations with body esteem. Design: Questionnaire study using the Body-Esteem Scale (BES) and Cleft Research Questionnaire (CRQ). Participants: Self-selected participants from a Western Australian CL/P population across 3 age groups (n=359). Main outcome measures: The BES is comprised of 3 factors: BE-Appearance, BE-Weight and BE-Attribution. Study mean BES factor scores were compared to normative non-cleft scores. Regression analysis was used to determine significant associations within each age group between BES factor scores and CRQ variables of: gender, self-reported body weight category, cleft type and importance of facial appearance rating. Results: Study mean BE-Attribution scores were significantly lower than the normative scores and significantly lower than the mean BE-Appearance and BE-Weight factor scores within the same age groups of this study. Having a cleft type of lip and palate, being overweight, and placing a high importance on facial appearance had significant negative associations with BES scores. Maintaining a normal body weight and placing a lower level of importance on facial appearance had significant positive associations. Gender had no significant associations. Conclusion: In this study, the attribution aspect of body esteem had a greater negative impact on patients than their appearance and body weight. This has important implications for clinical treatment and support of patients.